Gene expression analyses of vitellogenin, choriogenin and estrogen receptor subtypes in the livers of male medaka (Oryzias latipes) exposed to equine estrogens. Issue 11 (11th February 2016) - Ishibashi, Hiroshi; Uchida, Masaya; Koyanagi, Akiko; Kagami, Yoshihiro; Kusano, Teruhiko; Nakao, Ayami; Yamamoto, Ryoko; Ichikawa, Nobuhiro; Tominaga, Nobuaki; Ishibashi, Yasuhiro; Arizono, Koji
Abstract: In the present study, we investigated transcriptional profiles of estrogen‐responsive genes, such as vitellogenins ( Vtg1 and Vtg2 ), choriogenins ( ChgL and ChgH ) and estrogen receptor subtypes ( ERα, ERβ1, and ERβ2 ), in the liver of male medaka fish ( Oryzias latipes ) that were exposed to six equine estrogens (1–300 ng l −1 ) for 3 days. Our quantitative reverse transcription‐polymerase chain reaction (RT‐PCR) analyses revealed that the expression levels of hepatic Vtg, Chg and ERα genes in male medaka responded to various types and concentrations of equine estrogens. The estrogenic potentials of the tested chemicals were in the order of equilin > 17β‐estradiol > equilenin > 17β‐dihydroequilin > 17β‐dihydroequilenin > 17α‐dihydroequilin > 17α‐dihydroequilenin, showing the higher estrogenic potential of equilin than that of 17β‐estradiol. Our results also showed that the estrogenicities of 17β‐dihydroequilin and 17β‐dihydroequilenin were more potent than that of 17α‐dihydroequilin and 17α‐dihydroequilenin. Furthermore, in gene expression analyses of hepatic ER subtypes, observations were made to note that 17β‐estradiol and equilin induced ERα transcription in male medaka, and the ERα transcription level had significantly positive correlations with the expression of Vtg and Chg genes. In contrast, in the same 17β‐estradiol and equilin treatment groups, it was shown that the transcription levels of hepatic ERβ1 and/or ERβ2 had significantly negative correlations with the expression of Vtg and Chg genes. These results suggested some potential involvement of the ER subtypes in the regulation of Vtg and Chg gene expressions in the liver. This is the first report describing the comprehensive analyses of in vivo estrogenicity of the equine estrogens in male medaka. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : No comprehensive data are yet available regarding the estrogenic potentials and risks of equine estrogens to aquatic organisms. We carried out expression analyses on estrogen‐responsive genes in the livers of male medaka ( Oryzias latipes ) that were exposed to the equine estrogens for 3 days. Our qRT‐PCR analyses revealed that the expression levels of hepatic estrogen‐responsive genes in male medaka responded to various types and concentrations of equine estrogens. This is the first report describing the comprehensive analyses of in vivo estrogenicity of the equine estrogens in male medaka.